Transformasi Bambu Menuju Ekonomi Sirkular: Analisi Terhadap Sinergi Program CSR dan Peran Pemuda Desa Banu Ayu, Sumatera Selatan - Iqbal, Iqbal; Rasyifah, Maisyah Nur (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2025)
This study aims to analyze the impact of the application of appropriate technology in the development of bamboo processing business into skewers as a form of CSR program in Banu Ayu Village, Ogan Komering Ulu Regency, South Sumatra Province. The method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that the machine assistance provided by PT PT Pertamina Patra Niaga Fuel Terminal Baturaja was able to create a new transformation in the progress of village community development, especially young people with minimal educational backgrounds, making it difficult to find jobs. However, with business assistance and creativity development from bamboo can open up job opportunities for them. Not only that, there are positive impacts in business management and social aspects through this transformation, such as improved production systems and increased collaboration between residents, village government and the private sector. This bamboo transformation also creates a circular economy pattern because the upstream to downstream process is clearly done so as not to harm the environment and any party in the process of activity. This program is a clear example of the synergy between local potential and technology in creating economic independence for rural communities.